Predictors of treatment failure following early antibiotic discontinuation in culture-negative, ventilator-associated pneumonia: an observational study - Bien Huu Thien Le; Anh Tuan Mai; Megan D Phan (Journal of Infection in Developing Countries)
Introduction: Early antibiotic discontinuation in clinically suspected ventilator-associated pneumonia (VAP) may lead to infection relapse/recurrence and increase mortality. This study aimed to evaluate the incidence and potential predictors of treatment failure with this approach.